Face and Content Validity of Variables Associated with the Difficult-to-Sedate Child in the Pediatric Intensive Care Unit: A Survey of Pediatric Critical Care Clinicians - Lebet, Ruth M. (Aust Crit Care, 2018)
BACKGROUND: Clinicians recognize that some critically ill children are difficult-to-sedate. It may be possible to identify this clinical phenotype for sedation response using statistical modeling techniques adopted from machine learning. This requires identification of a finite number of variables to include in the statistical model. OBJECTIVE: To establish face and content validity for 17 candidate variables identified in the international literature as characteristic of the difficult-to-sedate child phenotype. METHODS: Pediatric critical care clinicians rated the relevance of 17 variables characterizing the difficult-to-sedate child using a four-point scale ranging from not (1) to highly relevant (4). Face and content validity of these variables were assessed by calculating a mean score for each item and computing an item-level content validity index. Items with a mean score >1 were rated as having adequate face validity. An item-level content validity index ≥0.70 indicated good to excellent content validity. SETTING AND PARTICIPANTS: Web-based survey emailed to members of the Pediatric Acute Lung Injury & Sepsis Investigators Network or the Society of Critical Care Medicine Pediatric Sedation Study Group. RESULTS: Of 411 possible respondents, 121 useable surveys were returned for a response rate of 29%. All items had a mean score >1, indicating adequate face validity. Ten of 17 items scored an item-level content validity index ≥0.70. The highest scoring items were requiring three or more sedation classes simultaneously, daily modal sedation score indicating agitation, sedation score indicating agitation for 2 consecutive hours, receiving sedatives at a dose >90th percentile of the usual starting dose and receiving intermittent paralytic doses for sedation. CONCLUSIONS: Computation of an item-level content validity index validated variables to include in statistical modeling of the difficult-to-sedate phenotype. The results indicate consensus among pediatric critical care clinicians that the majority of candidate variables identified through literature review are characteristic of the difficult-to-sedate child.